A People's Sense of Sacred: Catholic Identity and its Relationship to the Catholic Church Building - Turner, Joseph William (My University, 1997)
This thesis examines the Catholic identity of seventy Roman Catholics and how they see that identity expressed in their church buildings. These Catholics have conveyed strong emotions about their relationship with the God they have come to experience in their churches. Since the Second Vatican Council, many of their familiar religious symbols and ceremonies have been adjusted, removed or replaced. This has often left the participants expressing confusion or hurt.
This thesis recommends that pastors and liturgists benefit from some of the applied methodologies of cultural anthropology by listening to the voices of their parishioners and by sharing in their feelings that reflect the importance of these symbols. It is proposed that change and renewal may be more successful when such a process is employed.
The author interviewed forty Catholics in his own parish, a parish he knew well. Later, thirty other Catholics were asked to contribute their input. These additional voices were chosen from three parishes that had different experiences of the liturgical renewal as it affected their church buildings. The entire interview procedure took six months to complete.
The author does not propose that these seventy Catholics represent the opinions of all Catholics on the topic of Catholic identity. Proper cultural anthropological technique would demand a much longer exposure to the customs and experience of even these Catholics so that richer field notes could be assembled. The author was also aware of bias that may have existed in his role of priest/interviewer talking to parishioner/Catholic. These concerns were kept in mind as the work proceeded.
What does emerge from the research is the benefit of applying social science methodology to Christian ministry. The process of critical self-reflection affects the minister and his/her relationship with the congregation. Relationships can lead to trust, healing and understanding. The major conclusion of this research indicates that when these three elements are active, a more successful implementation of liturgical reform will be possible.
The statements that have been made by these Catholics about their Catholic identity may have a much broader implication. It may prove beneficial compare them to the voices that are heard from other congregations. The results of such studies may yield similar results concerning religious identity as it relates to the experience of the house of God.
Keywords: Religion; Religion